2019
DOI: 10.3389/fpls.2019.00912
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Engineering in Forest Trees

Abstract: Wood is a renewable resource that is mainly composed of lignin and cell wall polysaccharides. The polysaccharide fraction is valuable as it can be converted into pulp and paper, or into fermentable sugars. On the other hand, the lignin fraction is increasingly being considered a valuable source of aromatic building blocks for the chemical industry. The presence of lignin in wood is one of the major recalcitrance factors in woody biomass processing, necessitating the need for harsh chemical treatments to degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 123 publications
1
101
0
Order By: Relevance
“…In particular, total lignin content and monomer composition can impact the technical and economic feasibility of using lignocellulosic biomass such as wood as a feedstock for biofuels or other goods (1)(2)(3). Modifying lignin content or composition could be accomplished in several ways, including genetic engineering (4)(5)(6)(7)(8) or environmental priming (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, total lignin content and monomer composition can impact the technical and economic feasibility of using lignocellulosic biomass such as wood as a feedstock for biofuels or other goods (1)(2)(3). Modifying lignin content or composition could be accomplished in several ways, including genetic engineering (4)(5)(6)(7)(8) or environmental priming (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Lignin content can also be modified through breeding approaches, taking advantage of natural variation to obtain significant trait gains, using well-established protocols and experimental designs (11,12). Moreover, recent sophisticated techniques such as genomic selection allow for accelerated breeding with considerable reduction in costs (7,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…It is a major contributor to woody biomass recalcitrance as it prevents the access of extracellular enzymes to the degradable sugar moieties. Thus, there is considerable interest in developing plants with reduced lignin content that do not incur a growth penalty (Chanoca et al , 2019) and SNPeffect‐identified SNPs can serve as potential tunable levers for controlling flux through this pathway. Indeed, growth‐related phenotypes have been reported for lignin biosynthetic genes flagged as having functional SNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, silencing lignin-associated 4CLs can have different effects on syringyl-to-guaiacyl lignin (S/G) ratio depending on the species, ranging from increases in tobacco, Arabidopsis , and switchgrass (Kajita et al, 1996; Lee et al, 1997; Xu et al, 2011), to little change in alfalfa (Nakashima et al, 2008), to decreases in and rice (Gui et al, 2011). Variable effects on S/G ratio have even been reported among closely related poplar species (Hu et al, 1999; Voelker et al, 2010; Chanoca et al, 2019 and references therein). Such variation has been attributed both to differing degrees of 4CL downregulation, as well as to 4CL multiplicity (Boerjan et al, 2003; Saballos et al, 2012).…”
Section: Introductionmentioning
confidence: 97%